OCT Applications in Ophthalmology - Lanza, Michele (Biomedical Engineering, 2018)
I am very proud and excited to introduce to you this book, which provides many interesting indications on how to better understand and handle the world of optical coherence tomography (OCT). Reading the chapters, you will be aware that this device is extremely important not just in the clinical practice of retinal diseases, but is also very useful as a surgical tool. Moreover, application of OCT has crossed the borders of the retina and is currently being applied to corneal diseases and glaucoma. I am confident you will find enough useful information to improve your practice using OCT and to provide a better quality of care for your patients.